Evaluation of who guided pain management protocol in cases of carcinoma cervix - Bindal, Jyoti; Agrawal, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pain in patients with cancer cervix is a complex process that occurs from many causes. Opioids, the major class of analgesic used in management of moderate to severe pain, are usually effective and have favorable benefit to risk ratio. Morphine is the most effective and commonly used opioid in cancer pain management. Methods: Patients of cancer cervix attending the Obstetrics and Gynecology Department, KRH for a period January 2016 to December 2016. 200 patients were included in the study. Pain intensity was measured by visual analogue scale. Results: Maximum number of subjects were in stage IIB (46%) followed by stage IIIB (42%). Minimum number of subjects were in stage IA and stage IVB. In stage I, 55.6% patients had mild pain, 27.8% had moderate and 16.7% patients had severe pain. In stage II, carcinoma cervix patients 80.4% patients had moderate pain and only 12% patients had severe pain and stage III, 47.6% patients had severe pain and stage IV all patients had severe pain. Most common site for pain was lower abdomen in carcinoma cervix patients. The pain was recorded as moderate in maximum (49%) subjects followed by severe (39%). Mild pain was seen only in 12% subjects. Maximum response was seen for Step III (95.1%) while minimum for Step II (44.1%). Conclusions: Pain is a common symptom in cancer cervix patients. Morphine is most useful drug in cancer pain management. It is easily titratable and has a favorable benefit to risk ratio.